2018
DOI: 10.15252/embr.201745535
|View full text |Cite
|
Sign up to set email alerts
|

Tel1/ ATM prevents degradation of replication forks that reverse after topoisomerase poisoning

Abstract: In both yeast and mammals, the topoisomerase poison camptothecin (CPT) induces fork reversal, which has been proposed to stabilize replication forks, thus providing time for the repair of CPT-induced lesions and supporting replication restart. We show that Tel1, the orthologue of human ATM kinase, stabilizes CPT-induced reversed forks by counteracting their nucleolytic degradation by the MRX complex. Tel1-lacking cells are hypersensitive to CPT specifically and show less reversed forks in the presence of CPT T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 59 publications
2
34
0
Order By: Relevance
“…Several groups reported that this clinically relevant, unscheduled nucleolytic degradation observed in BRCA-defective cancer cells is triggered by the remodeling of stalled forks into four-way junctions (Lemaç on et al, 2017;Mijic et al, 2017;Taglialatela et al, 2017). Analogously, Tel1-the yeast ATM ortholog-was recently reported to protect against degradation forks reversed upon topoisomerase I inhibition (Menin et al, 2018). Remarkably, using multiple genetic tools to interfere with replication fork remodeling (i.e., PARP inhibition and RAD51, SMARCAL1, or RECQ1 depletion), we found that the defects observed during unperturbed replication upon inac-tivation of RNF168 strictly depend on replication fork reversal.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups reported that this clinically relevant, unscheduled nucleolytic degradation observed in BRCA-defective cancer cells is triggered by the remodeling of stalled forks into four-way junctions (Lemaç on et al, 2017;Mijic et al, 2017;Taglialatela et al, 2017). Analogously, Tel1-the yeast ATM ortholog-was recently reported to protect against degradation forks reversed upon topoisomerase I inhibition (Menin et al, 2018). Remarkably, using multiple genetic tools to interfere with replication fork remodeling (i.e., PARP inhibition and RAD51, SMARCAL1, or RECQ1 depletion), we found that the defects observed during unperturbed replication upon inac-tivation of RNF168 strictly depend on replication fork reversal.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, replication stress in ATR-defective Schizosaccharomyces pombe and mammalian cells results in MRE11- and EXO1-dependent ssDNA accumulation ( Hu et al, 2012 ; Koundrioukoff et al, 2013 ; Tsang et al, 2014 ). Interestingly, in S. cerevisiae , Tel1/ATM was recently found to counteract nucleolytic degradation by Mre11 of replication forks that reverse upon treatment with camptothecin (CPT) ( Menin et al, 2018 ), which leads to accumulation of torsional stress by blocking Top1 on DNA ( Postow et al, 2001 ; Koster et al, 2007 ; Ray Chaudhuri et al, 2012 ). Fork reversal in CPT is promoted by the replisome component Mrc1, whose inactivation prevents fork reversal in both wild type and TEL1 deleted cells ( Menin et al, 2018 ).…”
Section: Nuclease Action At the Replication Forksmentioning
confidence: 99%
“…A role for telomerase at replication forks also argues that previously identified regulators of telomere length may exert their effects at collapsed forks, rather than fully replicated termini. For example, the role of the Mre11-Rad50-Xrs2 (MRX) complex in yeast telomere length regulation has long been assumed to be due to an end-processing activity at fully replicated termini (66,67); however, increasing evidence for a function for this complex at stalled replication forks suggests that MRX may regulate telomere length homeostasis by protecting fork integrity (68)(69)(70). This also argues for an alternative interpretation of the recent observation that there is a pathological interaction between replication forks and telomerase in RTEL1 -/-mammalian cells (71).…”
Section: Discussionmentioning
confidence: 99%